The effect of psychological capital and emotions on emoyional labor: A study on hotel employees - Dönmez, Selin (My University, 2019)
Individuals working in service sector usually arrange their emotions while in a relation with customers and they are forced to exhibit emotional labor to maximize customer satisfaction. Problem of the study is identification of the relationship between emotion and psychological capital and emotional labor acting strategies. Purpose of this study is investigation the influence of psychological capital and emotions on emotional labor. Importance of this study is to contribute the literature of emotional labor and psychological capital terms and drawing attention effects of psychological capital and emotions on emotional labor to catch attention of administrators. In this study, effect of psychological capital and emotions on emotional labor is researched with 158 individuals working in hospitality sector in Istanbul and Kayseri which includes intense emotional labor. In this study, questionnaire which is one of quantitative decision techniques is used to collect necessary data. According to findings of this study, there are significant relationship among emotional labor, positive and negative emotions and psychological capital. In addition to these results, hope has a significant effect on emotional labor and also, hope and positive emotions influence emotional labor. Limitations of this study is time and geographic limitations and for future researches, it is suggested that to gather more datas from each provinces of Turkey.

Hizmet sektöründe çalışan bireyler müşteri ilişkilerinde sıklıkla duygularını kullanmakta ve müşteri memnuniyetini maksimum seviyeye taşımak amacıyla duygusal emek göstermektedir. Duygusal emek kavramı Hochschild tarafından 1983 yılında literatüre kazandırılmış ve basitçe duyguların bedensel olarak gözlenebilir şekilde yönetilmesi olarak tanımlanmıştır. Literatürde birçok araştırmaya konu olan bu kavramın çalışma yaşamındaki bireylere birçok pozitif ve negatif etkisi bulunmaktadır. Bu araştırmanın amacı, duyguların ve psikolojik sermayenin duygusal emek üzerindeki etkisini araştırmaktır. Araştırmanın önemi, duygusal emek ve psikolojik sermaye kavramları hakkında yazına katkı sağlamak ve duygular ve psikolojik sermayenin duygusal emek davranışları üzerindeki etkisine dikkat çekerek insan kaynakları departmanına yarar sağlamaktır. Bu araştırmada, duygusal emeğin yoğun olarak bulunduğu sektörlerden otelcilik sektöründe çalışan bireylerin duyguları ve psikolojik sermayelerinin duygusal emek davranışları üzerindeki etkisi araştırılmıştır. Araştırmada nicel araştırma tekniklerinden anket kullanılmıştır. 2019 yılında İstanbul ve Kayseri ilinde bulunan otellerde görev yapan 158 çalışanın anket sonuçlarına dayanan bu araştırmada toplanan veriler IBM SPSS20 programı ile analiz edilmiştir. Araştırmanın sonucunda pozitif ve negatif duygu ve psikolojik sermayenin duygusal emek üzerinde anlamlı bir etkisinin bulunduğu, psikolojik sermayenin bileşenlerinden umudun duygusal emeği anlamlı şekilde etkilediği ve pozitif duygu ve umudun duygusal emek üzerinde anlamlı etkisi bulunmuştur.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Emotion; Emotional labor; Psychological capital